2006
DOI: 10.1182/blood-2006-10-051110
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of IGHV3-21–expressing B-cell chronic lymphocytic leukemia: an Italian multicenter study

Abstract: IGHV3-21-using chronic lymphocytic leukemia (CLL) is a distinct entity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
92
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 51 publications
7
92
4
2
Order By: Relevance
“…[3][4][5] Consistently, GEP studies performed by our group and comparison of IGHV3-21 CLL versus non-IGHV3-21 CLL have identified a restricted number of genes (122 probes corresponding to 115 genes) whose differential expression may explain, at least in part, the clinical aggressiveness of IGHV3-21 CLL. 3 By reviewing the list of the 122 probes differentially expressed by IGHV3-21 CLL, 1 we found SEPT10 among the 62 probes (59 genes) significantly downregulated in this CLL subset. 3 Downregulation of SEPT10 in IGHV3-21 CLL was an unexpected finding, because SEPT10 expression is considered a poor prognostic marker and IGHV3-21 CLL typically has poor clinical outcome.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…[3][4][5] Consistently, GEP studies performed by our group and comparison of IGHV3-21 CLL versus non-IGHV3-21 CLL have identified a restricted number of genes (122 probes corresponding to 115 genes) whose differential expression may explain, at least in part, the clinical aggressiveness of IGHV3-21 CLL. 3 By reviewing the list of the 122 probes differentially expressed by IGHV3-21 CLL, 1 we found SEPT10 among the 62 probes (59 genes) significantly downregulated in this CLL subset. 3 Downregulation of SEPT10 in IGHV3-21 CLL was an unexpected finding, because SEPT10 expression is considered a poor prognostic marker and IGHV3-21 CLL typically has poor clinical outcome.…”
supporting
confidence: 63%
“…1 We recently reported a comprehensive characterization of IGHV3-21-expressing CLL, a disease subset recognized as a specific poor prognosis category, given its clinical behavior mostly independent of IGHV gene mutation status. 3 In this respect, we and others have demonstrated that IGHV3-21 CLL, although frequently displaying a mutated (M) IGHV gene configuration, has an overall survival similar to poor-prognosis UM CLL. [3][4][5] Consistently, GEP studies performed by our group and comparison of IGHV3-21 CLL versus non-IGHV3-21 CLL have identified a restricted number of genes (122 probes corresponding to 115 genes) whose differential expression may explain, at least in part, the clinical aggressiveness of IGHV3-21 CLL.…”
mentioning
confidence: 86%
See 3 more Smart Citations